Strategy for enhancing stability and bioavailability of active lipid ingredients through nanoparticle technology: Review - Ikra Nurohman; Al-fira Putriyanti (Science Midwifery, 2026)
Background: Lipid-based active ingredients have high pharmacological potential, such as anti-inflammatory, antioxidant, and anticancer activities, but often face biopharmaceutical challenges such as low water solubility, poor chemical stability, and limited bioavailability. Objectives: This review article aims to analyze various nanoparticle technology-based formulation strategies to improve the stability and pharmacological activity of lipid active ingredients. Methods: A total of 31 scientific articles published between 2020 and 2025 were systematically analyzed to evaluate the types of lipid nanoparticle systems, production methods, the role of surfactants and additives, and their impact on stability and bioavailability. Commonly used systems include Solid Lipid Nanoparticles (SLN), Nanostructured Lipid Carriers (NLC), and nanoemulsions. Results: The results of the study indicate that encapsulation in a nano lipid matrix can protect the active ingredients from oxidative, photolytic, and enzymatic degradation and increase membrane solubility and permeability. Key factors for successful formulation include the selection of lipid type, production method, and the combination of surfactant and coating polymer. In addition to improving pharmacokinetic parameters, lipid nanoparticle systems also show potential for cost efficiency through dose reduction and increased therapeutic efficacy. Conclusions: Overall lipid nanoparticle technology is an effective, applicable and prospective approach in the development of modern pharmaceutical preparations based on lipophilic active ingredients.